2018
DOI: 10.1080/20445911.2018.1552700
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual complexity and ambiguity of verbal instructions on target identification

Abstract: Research has shown that visual complexity and the ambiguity of verbal information affect the speed and accuracy of locating targets during visual search. The higher the visual complexity and description ambiguity, the slower and poorer the target identification performance. Because these factors are seldom studied in combination (even though they regularly co-occur), it is unclear whether they would interact. Therefore, in two experiments, participants viewed images that displayed cartoon-like characters and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…For instance, experiments in cognitive science have shown that ambiguity can arise due to the visual context (e.g., multiple objects that the referent might refer to; Allopenna, Magnuson, & Tanenhaus, 1998;Eberhard, Spivey-Knowlton, Sedivy, & Tanenhaus, 1995), the lack of specificity of the verbal information (e.g., referring to a target without verbal location descriptions; Louwerse & Bangerter, 2010), or a lack of prior knowledge (e.g., lack of background knowledge about a to be inspected and discussed painting; Richardson, Dale, & Kirkham, 2007;Experiment 2). When verbal referents are ambiguous for any of those reasons, it will take listeners more time to locate the relevant (i.e., target) information, if they are able to locate it at all (Louwerse & Bangerter, 2010;Van Marlen, Van Wermeskerken, & Van Gog, 2018).…”
Section: The Role Of Verbal Ambiguity In the Effectiveness Of Emmementioning
confidence: 99%
“…For instance, experiments in cognitive science have shown that ambiguity can arise due to the visual context (e.g., multiple objects that the referent might refer to; Allopenna, Magnuson, & Tanenhaus, 1998;Eberhard, Spivey-Knowlton, Sedivy, & Tanenhaus, 1995), the lack of specificity of the verbal information (e.g., referring to a target without verbal location descriptions; Louwerse & Bangerter, 2010), or a lack of prior knowledge (e.g., lack of background knowledge about a to be inspected and discussed painting; Richardson, Dale, & Kirkham, 2007;Experiment 2). When verbal referents are ambiguous for any of those reasons, it will take listeners more time to locate the relevant (i.e., target) information, if they are able to locate it at all (Louwerse & Bangerter, 2010;Van Marlen, Van Wermeskerken, & Van Gog, 2018).…”
Section: The Role Of Verbal Ambiguity In the Effectiveness Of Emmementioning
confidence: 99%
“…Huang and Pashler [9] indicated that the difficulty of a visual search affected efficiency. Marlen et al [10] also found that high visual complexity and high verbal ambiguity resulted in a low accuracy and slow response time on visual search tasks. In this study, the white color was set for the without background context and scenery was set for the with background context.…”
Section: Number Of Fixationsmentioning
confidence: 98%
“…Huang and Pashler [9] also pointed out that the difficulty of the visual search test affects the search efficiency. According to Marlen et al [10], the background complexity and the clear or fuzzy description of the target affect the search speed and accuracy. It is concluded that the higher the complexity and description ambiguity are, the slower and harder it is to find the target.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, selecting visual information is done by looking at the information, so we can measure the selection process with an eye‐tracking device (Jarodzka et al., 2017 ; Kok & Jarodzka, 2017a ). Note here that looking at the relevant information is a necessary (but not sufficient) first step for organizing and integrating it with existing knowledge (Kok & Jarodzka, 2017b ): If a learner does not “follow” what the teacher is currently talking about, for example, if the teacher uses jargon that the learner does not know yet or if teachers verbal utterances are ambiguous, learners could have trouble locating the visual information related to the verbal information (Van Marlen, van Wermeskerken, & van Gog, 2019 ). This could lead to the learner missing (i.e., not selecting) important visual information and thus not organizing verbal and visual information together, and integrating it with existing knowledge.…”
Section: Introductionmentioning
confidence: 99%